Analysis of natural regeneration in four measurement plots of a tropical reserved forest of Tingo María - Gutiérrez Collao, Jairo Edson (2023)
The objective of the research was to know the dynamics of the reserved forest of Tingo María, through the analysis of the conditions of increase, mortality and recruitment; as well as the silvicultural conditions (lighting and shape of the canopy, stem quality and lianas infestation), in order to carry out the sustainable management of this forest. Four permanent measurement plots of 1 ha each were installed, divided into sub-plots for the evaluation of natural regeneration categories, such as saplings, low saplings, high saplings and stems. The results reported a total of 1487 individuals in the four PPMs, of which 761 individuals were in the stem category. The highest percentages of average annual increase, mortality and recruitment were recorded in the jumping category, with values of 2.2, 6.6 and 23.7%, respectively. Likewise, most individuals are free of lianas, reporting very straight and cylindrical stems, tolerable crown shape, but deficient crown lighting. In conclusion, the reserved forest requires silvicultural management to improve the shape of the canopy and its lighting, in order to favor the adequate growth of the individuals of natural regeneration.